General synthesis and definitive structural identification of MN4C4 single-atom catalysts with tunable electrocatalytic activities - Fei, H; Dong, J; Feng, Y; Allen, C; Wan, C; Volosskiy, B; Li, M; Zhao, Z; Wang, Y; Sun, H; An, P; Chen, W; et al. (Nature Publishing Group, 2018)
Single-atom catalysts (SACs) have recently attracted broad research interest as they combine the merits of both homogeneous and heterogeneous catalysts. Rational design and synthesis of SACs are of immense significance but have so far been plagued by the lack of a definitive correlation between structure and catalytic properties. Here, we report a general approach to a series of monodispersed atomic transition metals (for example, Fe, Co, Ni) embedded in nitrogen-doped graphene with a common MN4C4 moiety, identified by systematic X-ray absorption fine structure analyses and direct transmission electron microscopy imaging. The unambiguous structure determination allows density functional theoretical prediction of MN4C4 moieties as efficient oxygen evolution catalysts with activities following the trend Ni > Co > Fe, which is confirmed by electrochemical measurements. Determination of atomistic structure and its correlation with catalytic properties represents a critical step towards the rational design and synthesis of precious or nonprecious SACs with exceptional atom utilization efficiency and catalytic activities.